Implementation of RNS-based Chip Map on Spreading Method of Zigbee PHY Layer by Using Software-Defined Radio - Latin, Mukmin Maulana; Trio Adiono (Journal of System & Technology (SYSTEC), 2025)
This paper implements a Residue Number System (RNS)-based chip map in the Zigbee Direct Sequence Spread Spectrum (DSSS) PHY layer, based on the IEEE 802.15.4 standard. Simulations showed that RNS-based spreading sequences improve Bit Error Rate (BER) compared to standard Zigbee. To validate these findings and enable flexible experimentation, this work realizes the modified RNS-based design within a Zigbee transceiver system using Software Defined Radio (SDR). The system was modeled in LabVIEW and implemented on an Ettus X310 SDR platform. This platform allowed dynamic reconfiguration of sampling rate, carrier frequency, and chip maps, enabling rapid prototyping. Advanced synchronization and correlation techniques were incorporated to optimize signal detection and decoding. Extensive experiments were conducted to evaluate BER performance. Over-the-air testing confirms the effectiveness of the RNS-based spreading method, validating prior simulation results. The SDR platform's flexibility was crucial, allowing adaptation to varying channel conditions and real-time analysis. This work successfully demonstrates the benefits of RNS-based chip sequences in Zigbee and underscores the value of SDR for developing advanced wireless communication techniques.